Economics - Sloman, John (Harlow, England ; New York : Prentice Hall/Financial Times, 2006)
Comprehensive and completely up-to-date, this edition is the ideal introduction for students studying economics for the first time.
Includes bibliographical references and index.
obn 20/09/2018
Loans
Keywords: Economics